Eddy covariance evaluation of ecosystem fluxes at a temperate saltmarsh in Victoria, Australia, shows large CO2 uptake - R. Reef; E. Daly; E. Daly; T. Anandappa; E.-J. Vienna-Hallam; H. Robertson; M. Peck; A. Guyot; A. Guyot (Biogeosciences, 2025)
Recent studies have highlighted the important role of vegetated coastal ecosystems in atmospheric carbon sequestration. Saltmarshes constitute 30 % of these ecosystems globally and are the primary intertidal coastal wetland habitat outside the tropics. Eddy covariance (EC) is the main method for measuring biosphere–atmosphere fluxes, but its use in coastal environments is rare. At an Australian temperate saltmarsh site on French Island, Victoria, we measured CO2 and water gas concentration gradients, temperature, wind speed, and radiation. The marsh was dominated by a dense cover of Sarcocornia quinqueflora. Fluxes were seasonal, with minima in winter when vegetation is dormant. Net ecosystem productivity (NEP) during the growing season averaged 10.54 g CO2 m−2 d−1, decreasing to 1.64 g CO2 m−2 d−1 in the dormant period, yet the marsh remained a CO2 sink due to some sempervirent species. Ecosystem respiration rates were lower during the dormant period compared with the growing season (1.00 vs. 1.77 µmol<mspace width="0.125em" linebreak="nobreak"/>CO2<mspace width="0.125em" linebreak="nobreak"/>m-2<mspace width="0.125em" linebreak="nobreak"/>s-1<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="86pt" height="16pt" class="svg-formula" dspmath="mathimg" md5hash="7e6f89d93837a27d8d2ad1d00a028ffd"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="bg-22-1149-2025-ie00001.svg" width="86pt" height="16pt" src="bg-22-1149-2025-ie00001.png"/></svg:svg>), with a slight positive relationship with temperature. During the growing season, fluxes were significantly influenced by light levels, ambient temperatures, and humidity, with cool temperatures and cloud cover limiting NEP. The ecosystem water use efficiency of 0.86 g C kg−1 H2O was similar to other C3 intertidal marshes, and evapotranspiration averaged 2.48 mm d−1 during the growing season.